SISTEM INFORMASI PENJUALAAN TOKO BUTIK MELYSA SHOP - safitri mediawati; Emmy Wahyuningtyas (Informatics Department-Universitas Wijaya Kusuma Surabaya, 2022)
Melysa shop boutique shop is a store that sells women's clothing and accessories located in Gresik city. Currently, the Melysa shop boutique shop wants to increase its sales by expanding its sales to all regions of Indonesia to seek greater profits. However, the lack of a sales strategy causes the products sold to be less interested. Therefore, this store requires a sales information system by recommending goods with a high level of sales and querying views that are often viewed. The result achieved is a system that can assist shop owners in selling their products in which there are customer data, category data, product data, sales reports, and product recommendations. This system is made based on a website with the PHP programming language and My Sql database. Keywords: Information system, Sales, Website, PHP, Mysql